Prolonged Grief Disorder Among Refugees in Psychological Treatment—Association With Self-Efficacy and Emotion Regulation - Lacour, Oriane; Morina, Naser; Spaaij, Julia; Nickerson, Angela; Schnyder, Ulrich; von Känel, Roland; Bryant, Richard A.; Schick, Matthis (Frontiers in Psychiatry, 2020)
Background: While Prolonged Grief Disorder (PGD) among refugees has recently started to attract scientific attention, knowledge regarding associated psychological factors remains limited. Given the multifactorial context of persecution, trauma, displacement and exile-related difficulties, obtaining a better understanding of PGD in refugees is crucial because PGD may affect psychological well-being, level of functioning and social integration. Methods: In a sample of refugees receiving psychological treatment in Switzerland (N=88), we examined the relationship between severity of PGD and potentially associated factors such as emotion regulation, perceived self-efficacy, as well as potentially traumatic events and post-migration living difficulties. Results: In a regression analysis, difficulties in emotion regulation and lower perceived self-efficacy were associated with greater severity of PGD, while post-migration living difficulties and potentially traumatic events did not emerge as significant factors. Conclusion: These findings suggest that emotion regulation and perceived self-efficacy are associated with PGD in refugees in psychological treatment, and are thus potential targets for treatment interventions.